Dinâmica do fluxo e de reservatórios de carbono de três morfotipos de Paubrasilia echinata Lam. na fase juvenil e adulta, sob irradiância contrastante - Martins, Carlos Augusto Pagotto (2019)
In view of the need to generate more knowledge about the best conditions for reforestation with native species, their preservation and on the quality of the wood used in the making of arches for string musical instruments, this work had as objective to evaluate the gas exchanges and the size of the carbon reservoirs of three morphotypes of Paubrasilia echinata Lam. in the juvenile and adult phases, under high and low irradiance. To achieve this purpose, two experiments were carried out. The first one analyzed photosynthesis and structural carbon (cell wall) structures in leaves and stems of juvenile plants of the small, medium and large morphotypes of P. echinata exposed to full sun and artificial shade. In the second experiment, the same variables of the first experiment were also analyzed, however, in adult plants of the three morphotypes with 12 year-old planted in full sun and natural shade under a forest of Atlantic forest fragment. The nonstructural carbohydrate contents (glucose, fructose, sucrose and starch) were analyzed only in the second experiment. Juvenile plants of the three morphotypes presented low levels of cellulose in the two light conditions. The medium and large morphotypes invested more in the production of cellulose and foliar hemicellulose in the shade, while in the full sun there was a greater increase of lignin. Adult plants of the three morphotypes presented higher levels of lignin in the stems and leaves in full sun. In the stems of adult plants, a lower concentration of soluble sugars (glucose and fructose) and a higher accumulation of sucrose and starch were observed in medium and large morphotypes in the full sun. The assimilation of CO2, stomatal conductance, transpiration and water use efficiency showed better performance of the small morphotype in the shade while the medium and large morphotypes, in full sun, in both juvenile and adult plants. In view of these results, the functional classification of the medium and large morphotypes as heliophiles and the small morphotype as umbrófilo is evident